2012
DOI: 10.1183/09031936.00051512
|View full text |Cite
|
Sign up to set email alerts
|

Chest computed tomography: a validated surrogate endpoint of cystic fibrosis lung disease?

Abstract: Clinical trials for the treatment of cystic fibrosis (CF) lung disease are important to test and optimise new therapeutic interventions. To evaluate the effect of these interventions, sensitive and accurate outcome measures are needed. The most commonly used endpoints are spirometric variables such as the forced expiratory volume in 1 s and respiratory tract exacerbations. Unfortunately, these endpoints are relatively insensitive for monitoring progression of CF lung disease, and thus require a large number of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
41
0
7

Year Published

2014
2014
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(48 citation statements)
references
References 166 publications
(196 reference statements)
0
41
0
7
Order By: Relevance
“…However, spirometry is difficult to be performed by preschoolers and infants, not only because it requires special equipment [17,18], but also because FEV 1 is now of less value in monitoring children with CF, due to its lack to assess early or mild CF lung disease [19][20][21][22]. Structural damages may be present in High Resolution Computed Tomography (HRCT) in one third of CF children with normal spirometry [20][21][22][23][24][25].…”
Section: Introductionmentioning
confidence: 99%
“…However, spirometry is difficult to be performed by preschoolers and infants, not only because it requires special equipment [17,18], but also because FEV 1 is now of less value in monitoring children with CF, due to its lack to assess early or mild CF lung disease [19][20][21][22]. Structural damages may be present in High Resolution Computed Tomography (HRCT) in one third of CF children with normal spirometry [20][21][22][23][24][25].…”
Section: Introductionmentioning
confidence: 99%
“…24 Several studies have shown that despite stable spirometric parameters, HRCT scores show annual progression in total CT score. 7 Despite the well-established importance of HRCT scores for CF, few studies have made reference to these scores in different microbiological groups, 11 with no published data regarding MRSA colonized patients. In this context, our study highlights the importance of HRCT scores in CF patients with chronic colonization with MRSA, thus making a significant contribution towards aiding clinicians who deal with this group of patients.…”
Section: Discussionmentioning
confidence: 99%
“…7 Imaging examinations are able to detect early disease progression, thereby contributing to treatment effectiveness and quality of life among CF patients. Furthermore, HRCT can be used both for patients who are unable to undergo spirometry and for analysis on the two tests, since HRCT shows early changes in patients with normal spirometry.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations